Genetic analysis of genes associated with Mendelian dementia - Dautaj, Astrit; Mandarà, Luana; Tassi, Vittorio; Dhuli, Kristjana; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim: Dementia is a disease associated with cognitive and/or behavioral changes that interfere with the ability to perform daily activities. Alzheimer’s disease is the most common type of dementia. The aim of this mini-review is to summarize all the syndromes characterized by dementia and for which the associated gene is known. Methods: We searched those syndromes in PubMed and OMIM database. Results: Two forms of dementia exist: the multifactorial dementia results from the interaction of different genetic and environmental factors, the hereditary dementia associated with a single gene. Individuals with a family history of dementia and early onset of the disease are more likely to have a hereditary form of dementia. Dementias are mainly autosomal dominant, but they can also be autosomal recessive or X-linked. Conclusions: Since dementia has high clinical and genetic heterogeneity, the use in diagnostics of a large panel of genes may greatly help to speed up the determination of the molecular diagnosis and/or establish a risk of recurrence in family members for the purpose of planning appropriate preventive and/or therapeutic measures.